Cardiotoxicity induced by Arsenic Trioxide in a patient with acute promyelocytic leukemia. A case report - Cruz RodrÃguez, Rodolfo Antonio; Acuña Caballero, Martha del Carmen; Portell Betancourt, Lizmaureen; Cabrera Zamora, Maritza Margarita (Revista Científica Estudiantil UNIMED, 2021)
Arsenic trioxide has been used in the treatment of acute promyelocytic leukemia with good results in the hematological remission of this malignant hemopathy, but in spite of its effectiveness it can bring various adverse reactions such as cardiotoxicity. The present work had as objective to describe Long QT Syndrome as an adverse reaction to the treatment with arsenic trioxide in a patient with acute promyelocytic leukemia. A case of an 81-year-old patient treated with arsenic trioxide in the Hematology service of the Dr. Gustavo Aldereguía Lima Hospital in Cienfuegos was presented, in which Long QT Syndrome was confirmed by electrocardiography as secondary cardiotoxicity to this treatment.